2013
DOI: 10.5455/medarh.2013.67.460-463
|View full text |Cite
|
Sign up to set email alerts
|

New Views on Cesarean Section, its Possible Complications and Long-Term Consequences for Children's Health

Abstract: Historical developments and advancements in cesarean section techniques and logistics have reduced the maternal and neonatal risks associated with the procedure, while increasing the number of operatively completed pregnancies for medically unjustifiable reasons. The uncritical attitude towards cesarean section and the fast emergence of ‘modern’ diseases such as obesity at a young age, asthma, type 1 diabetes mellitus and various forms of dermatitis have stimulated researches associating cesarean section with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 12 publications
2
28
0
1
Order By: Relevance
“…However, while it is well-established that physical activity improves birth outcomes [9][10][11], studies looking at the relationships between objective assessments of fitness and delivery type, gestational age, duration of labour stages, birth weight and values of umbilical cord blood gas are limited. The causes of caesarean sections and how to reduce caesarean section rates are now a spotlight of research as this type of delivery has been associated with an increased risk of infection compared with vaginal deliveries, higher wound dehiscence, haemorrhage and reduced fertility [12][13][14], as well as an increased risk of allergies, type 1 diabetes or respiratory problems [15] in infants, among other complications. Furthermore, it is noteworthy that in 2016 in Spain there were 22% caesarean sections in public hospitals [16], higher than the 15% rate recommended by the World Health Organization [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, while it is well-established that physical activity improves birth outcomes [9][10][11], studies looking at the relationships between objective assessments of fitness and delivery type, gestational age, duration of labour stages, birth weight and values of umbilical cord blood gas are limited. The causes of caesarean sections and how to reduce caesarean section rates are now a spotlight of research as this type of delivery has been associated with an increased risk of infection compared with vaginal deliveries, higher wound dehiscence, haemorrhage and reduced fertility [12][13][14], as well as an increased risk of allergies, type 1 diabetes or respiratory problems [15] in infants, among other complications. Furthermore, it is noteworthy that in 2016 in Spain there were 22% caesarean sections in public hospitals [16], higher than the 15% rate recommended by the World Health Organization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Acetate, butyrate, and propionate (SCFA) modulate the gene expression in host, modifying the infant microbiome and stimulating white blood cells [65]. Some studies suggested that infants born by cesarean section are at greater risk of developing obesity and/ or diabetes than those born vaginally [66]. Other studies with preschool children showed overweight or obesity in children born by cesarean [67], while in other showed the opposite [68].…”
Section: Gut Microbiota and Diabetes Typementioning
confidence: 99%
“…Grundlage hierfür ist die Programmierung der Hypothalamus-Hypophysen-Nebennierenrinden-Achse, die zu einer vermutlich lebenslangen Modulation des metabolisch endokrinen Systems führt. Zusätzlich konnten einige Metaanalysen belegen, dass das Risiko für frühkindliches Asthma und für einen frühkindlichen insulinpflichtigen Diabetes mellitus Typ 1 nach Schnittentbindung jeweils um 20 % erhöht ist [19]. Prinzipiell müssen somit auch unterschiedliche fetale Hormonkonzentrationen und Zusammensetzungen zum Zeitpunkt der Geburt und in den ersten Lebenswochen oder die Exposition des Säuglings gegenüber bestimmten Bakterienstämmen während der vaginalen Entbindung als mögliche Einflussfaktoren für eine spontane Eröffnung der bei etwa 90 % aller Kinder zum Zeitpunkt der Geburt vorhandenen Hasner-Membran diskutiert werden.…”
Section: Diskussionunclassified